COMPLIANCE RESEARCH CONCEPTS AS A BASIS FOR UNDERSTANDING ADHERENCE TO TREATMENT IN PATIENTS WITH MYOCARDIAL INFARCTION - Андрей Георгиевич Петров; Сергей Николаевич Филимонов; Николай Владимирович Абрамов; Виктор Андреевич Семенихин (Медицина в Кузбассе)
The review is devoted to topical issues of the concept of compliance research as the basis for understanding adherence to treatment in patients with myocardial infarction. The significance of various factors influencing the doctor-patient relationship is shown, allowing to increase adherence to the treatment of a patient with myocardial infarction.